Bringing Technology Invention Products to the Market - Bambang S. Pujantiyo (Jurnal Inotera, 2022)
Bringing the invention of technology-based research results so that they can be commercialized, is closely related to the synergy of the triple helix Academician – Businessman – government (ABG) collaboration. In Indonesia, it has been done a lot, but it has not been able to have a significant impact. Collaboration is the initial activity of the commercialization process of technological inventions. This process is based on the Randal Goldsmith model which consists of 3 stages; investigation – development – commercialization. In this study, the update is at the development stage or validation stage which includes, production trials, market tests, and selling tests. After being applied in several research institutions, the results were obtained that the invention passed more significantly compared to before. With these results, it can be concluded and recommended that the proposed process method, can be used nationwide